Geochemistry of the Potassic Basalts from the Bufumbira Volcanic Field in Southwestern Uganda. - Barifaijo, E.; Muwanga, A.; Schumann, A. (My University, 2010)
Bufumbira volcanic field is the southernmost of the four Ugandan small Pleistocene to Recent volcanic fields within the western branch of the East African rift system. The rocks consist of silica undersaturated and vesicular basalts with numerous primary structures. The rocks consist of basanites, leucitites, olivine basalts, trachytes, tephrites, trachyandesites and andesites. The basalts are picritic in the northern part of the field where they are dominated by olivine and are clinopyroxene rich in the southern part of the field. Leucite and plagioclase are common in the groundmass in varying proportions by volume for the entire field. Type 1 dunite and wehrlite upper mantle xenoliths characterize the northern part of the field whereas type II clinopyroxenite xenoliths are common in the southern part of the field. The various basalts are low in SiO2 wt %, Al2O3 wt % and Na2O wt % but high in MgO wt %, TiO2 wt %, CaO wt %, K2O wt % with K2O/Na2O = 1.08 to 2.07. These are potassic belonging to the kamafugite series. Plots discriminate two geochemical trends corresponding to the picritic and clinopyroxene rich basalts. The diagram of Na2O + K2O wt. % against SiO2 wt. % enables various rocks to plot in the designated fields for the different alkaline basalts. The field is enriched in trace, light rare earth (LREE) and high field trace elements (HFSE) where La/Yb = 31 – 55. The petrographic and geochemical studies elucidate enrichment of the upper mantle by both mineralogical (modal) and cryptic (geochemical) metasomatism.
Keywords: Basalts, Enrichment, Mantle, Metasomatism, Potassic